EL MÉTODO DE PROYECTOS COMO TÉCNICA DIDÁCTICA EN EL CURSO: SEMINARIO INTEGRADO DE ALTA GERENCIA Y CÁTEDRA EMPRESARIAL - Alvarado Boirivant, Jorge (2011)
Teaching strategies are a series of actions carried out by the instructor with clear and explicit pedagogical intention. The foundations of these strategies lie on pedagogical knowledge and fall into two basic areas, namely; learning (learner‘s perspective) and instruction (professor‘s perspective).  This paper focuses on the project method as an instructional strategy applied in university course. Details on how the learners stimulate their strongest abilities and develop new ones are presented. This skill-building process prevents and solves interpersonal conflicts while creating both a favorable atmosphere and self-confidence which allows development of their own skills.